Tourism, creativity and talent: breaking Algarve’s tourism lock-in - Cruz, A. R. (2014)
Over the past decades creative and cultural activities have had modest opportunity to develop and grow in Algarve (Portugal) due to the tourism specialization in ‘sun and sand’. The regional dynamics based in this specific tourism product created path dependencies and limited opportunities for expansion and consolidation of the cultural and creative sector. Using the model of three Ts – talent, technology, tolerance – this short article presents the relative creative potential of Algarve, and opportunities to diversify the tourism offer attracting talented people and breaking the regional economic lock-in.